Biogeographical variation in antimicrobial resistance in rivers is influenced by agriculture and is spread through bacteriophages. (7th July 2022) - Andersson, Tilde; Adell, Aiko D.; Moreno‐Switt, Andrea I.; Spégel, Peter; Turner, Charlotta; Overballe‐Petersen, Søren; Fuursted, Kurt; Lood, Rolf
Abstract: Antibiotic resistance is currently an extensive medical challenge worldwide, with global numbers increasing steadily. Recent data have highlighted wastewater treatment plants as a reservoir of resistance genes. The impact of these findings for human health can best be summarized using a One Health concept. However, the molecular mechanisms impacting resistance spread have not been carefully evaluated. Bacterial viruses, that is bacteriophages, have recently been shown to be important mediators of bacterial resistance genes in environmental milieus and are transferrable to human pathogens. Herein, we investigated the biogeographical impact on resistance spread through river‐borne bacteriophages using amplicon deep sequencing of the microbiota, absolute quantification of resistance genes using ddPCR, and phage induction capacity within wastewater. Microbial biodiversity of the rivers is significantly affected by river site, surrounding milieu and time of sampling. Furthermore, areas of land associated with agriculture had a significantly higher ability to induce bacteriophages carrying antibiotic resistance genes, indicating their impact on resistance spread. It is imperative that we continue to analyse global antibiotic resistance problem from a One Health perspective to gain novel insights into mechanisms of resistance spread.